B-CN / P-CN homogeneous heterojunction with local electronic difference and uniform dispersion as well as construction method and application of B-CN / P-CN homogeneous heterojunction

By constructing a B-CN/P-CN homogeneous heterojunction with local electron differences, and using a built-in electric field to promote the migration of photogenerated carriers, the shortcomings of carbon nitride polymers in the field of photocatalysis are solved, and the photocatalytic performance and the degradation efficiency of rhodamine B are significantly improved.

CN119500226APending Publication Date: 2025-02-25NINGDE NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411666292.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing carbon nitride polymers have shortcomings in the field of photocatalytic organic degradation, such as low crystallinity, high exciton binding energy, and severe photogenerated carrier recombination, which limits their application.

Method used

B-CN/P-CN homogeneous heterojunction with local electron differences and uniform dispersion is constructed by a two-step calcining method with predoping and molten salt assisted, forming a built-in electric field to promote the directional migration of photogenerated carriers.

Benefits of technology

The photocatalytic performance is significantly improved, especially in the degradation of rhodamine B, the degradation rate reaches 97.5%, the degradation rate constant is 1.5 times that of pure phase CN, and good stable performance is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500226A_ABST
    Figure CN119500226A_ABST
Patent Text Reader

Abstract

The invention discloses a B-CN / P-CN homogeneous heterojunction with local electron difference and uniform dispersion as well as a construction method and application thereof, and belongs to the technical field of photocatalytic reaction materials. A simple pre-doping and fused salt assisted two-step calcination method is adopted, firstly, an electron-deficient body (boron) and an electron-rich body (phosphorus) are pre-doped in a precursor respectively, the electronic structure of a carbon nitride intermediate is regulated and controlled, then a KCl / LiCl salt mixture is used as a liquid reaction medium, and a B-CN / P-CN homogeneous heterojunction with local electron difference and uniform dispersion is constructed; additional acceptor impurities and donor impurities are generated through doping of B and P, the electronic structure of carbon nitride is changed, and a built-in electric field is formed at the interface of B-CN and P-CN, so that directional migration of photo-generated carriers and the separation efficiency of photo-generated carrier current are promoted, the photocatalytic performance of the material is greatly improved, and the photocatalytic performance of the material is improved. The prepared RhB photocatalyst has excellent RhB photocatalytic degradation performance under visible light irradiation, the degradation rate can reach 97.5%, the degradation rate constant is 1.5 times that of pure-phase CN, and the RhB photocatalyst has good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalytic reaction materials, and specifically relates to a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion, and a construction method and application thereof. Background Art

[0002] Rhodamine B, also known as Rose Red B or alkaline rose essence, commonly known as flower pink, is a synthetic dye with a bright pink color. It belongs to the triphenylmethane dyes and is widely used in the textile, printing, food and cosmetics industries. The dye wastewater has high chromaticity and poor biodegradability. If it is directly discharged without treatment, it will cause persistent deterioration of the water environment and cause serious harm to human kidneys, reproductive system, eyes and other organs, and even cause cancer. Therefore, it is urgent to develop an effective method for degrading the organic pollutant Rhodamine B in wastewater.

[0003] At present, the treatment methods of Rhodamine B at home and abroad mainly adopt the combination of physicochemical method and biochemical method. That is, the wastewater is pretreated by physicochemical method, and then enters the biochemical system, and finally discharged after being treated by physicochemical and biological filter tanks. Physicochemical treatment includes: precipitation method, adsorption method, electrochemical method, magnetic separation method, advanced oxidation method, evaporation concentration method, etc.; biochemical treatment includes: anaerobic treatment method (UASB, IC, two-stage anaerobic method), anaerobic-aerobic treatment method, anaerobic-photosynthetic bacteria treatment method, deep aeration, deep well aeration method, etc. However, these methods are complex in process, long in treatment time (ranging from more than ten days to dozens of days), and high in cost. The common method for treating Rhodamine B now is photocatalytic degradation.

[0004] Photocatalytic technology is a green technology with important application prospects in the fields of energy and environment. In recent years, the research and development of photocatalytic application technology has been very rapid. This new technology has the advantages of low energy consumption, simple operation process, mild reaction conditions, etc. It can completely oxidize organic matter in water, air and soil into non-toxic and harmless substances at room temperature, avoiding secondary pollution. In particular, it has outstanding performance in degrading organic pollutants, and can effectively degrade a variety of organic wastewaters including antibiotic pharmaceutical wastewater, sulfur-containing fuel wastewater, fermentation production wastewater, fine chemical wastewater, etc., to meet emission standards.

[0005] As a non-metallic semiconductor photocatalyst, carbon nitride polymer (PCN) has many advantages, such as good visible light response, suitable bandgap, good redox ability, easy preparation, low cost and environmental protection. Since Wang's research group first proved in 2009 that carbon nitride polymer can decompose water to produce hydrogen under visible light, a research boom of carbon nitride polymer in the field of photocatalysis has been set off, especially in the catalytic degradation of organic pollutants. However, with the continuous deepening of research work, it was found that the bulk carbon nitride polymer prepared by direct simple thermal polymerization of cyanamide precursors has the disadvantages of low crystallinity, high exciton binding energy, serious recombination of photogenerated carriers and low crystallinity, which seriously restricts its further application in the field of photocatalytic organic degradation.

[0006] To this end, researchers have carried out a lot of modification work on it. Among them, element doping, especially doping with non-metallic elements (such as boron (B), oxygen (O), phosphorus (P), sulfur (S), etc.) has been shown to improve the performance of carbon nitride in photodegradation of organic matter. When non-metallic elements are introduced into the carbon nitride structure, they usually change the distribution of electrons around the doping site, and can also cause the distortion of the catalyst structure and destroy its symmetry, thereby causing some originally degenerate energy levels to split, thereby reducing its band gap width and improving its light absorption performance. In addition, constructing a heterojunction between carbon nitride and another component material has also been shown to be the main strategy to promote the efficiency of photogenerated carrier separation.

[0007] At present, many successful cases such as CdS / g-C3N4, BiOCl / g-C3N4, graphene / g-C3N4 and MOF / g-C3N4 have been constructed to improve photocatalytic performance. However, this type of heterojunction structure still has some limitations, such as the Coulomb force and resistance between the interfaces of different materials, which will hinder the transfer of its charge. Therefore, researchers have proposed another built-in electric field model, that is, a homojunction composed of carbon nitrides with different energy levels. Due to the similar chemical structure, the resistance at the interface is much lower, which is more conducive to the migration of photogenerated carriers. Xia et al. designed and synthesized porous CN rods with triazine-heptazine homojunctions by the molten salt method. The study showed that the built-in electric field caused by the triazine-heptazine homojunction enhanced the separation of photogenerated charges, thereby improving its photocatalytic hydrogen production performance. Li et al. designed and synthesized P-doped carbon nitride / O-doped carbon nitride heterojunctions for photocatalytic-self-Fenton reaction. The results showed that the efficient heterojunction induced by the internal electric field improved the yield, utilization and degradation performance of H2O2.

[0008] Inspired by the above work, and taking into account that the synthesis of carbon nitride polymers by thermal polycondensation first forms many intermediates, which are then further polymerized into large carbon nitride polymers as the temperature rises, based on the opportunity provided by this synthesis process to regulate its local electronic structure, a homogeneous heterojunction with local electronic differences and uniform dispersion is constructed. By forming a built-in electric field to promote the directional migration of photogenerated carriers, it has good photocatalytic performance and the ability to photocatalytically degrade organic pollutants. It has broad application prospects and important reference significance in the field of sewage purification. Summary of the invention

[0009] In order to solve the problems existing in the prior art, the present invention provides a B-CN / P-CN homogeneous heterojunction with local electronic difference and uniform dispersion, and a construction method and application thereof, wherein additional acceptor impurities and donor impurities are generated by doping with B and P, the electronic structure of carbon nitride is changed, and a built-in electric field is formed at the interface of B-CN and P-CN, thereby promoting the directional migration of photogenerated carriers and the separation efficiency of photogenerated carriers, thereby greatly improving its photocatalytic performance.

[0010] The technical solution of the present invention is as follows:

[0011] One of the purposes of the present invention is to provide a method for constructing a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion, adopting a method of simple pre-doping and molten salt-assisted two-step calcination, firstly pre-doping electron-deficient bodies and electron-rich bodies in the precursor respectively, regulating the electronic structure of the carbon nitride intermediate, and then using a KCl / LiCl salt mixture as a liquid reaction medium to construct a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion.

[0012] Furthermore, the method specifically includes the following steps:

[0013] S1. Weigh melamine and sodium tetraphenylborate, grind them in a mortar, mix them thoroughly and evenly, transfer them into a ceramic crucible, place them in a muffle furnace and heat them in an air atmosphere, then cool them naturally to room temperature, and grind them into powder, namely B-melem;

[0014] S2, weighing melamine and sodium dihydrogen phosphate, grinding them in a mortar, mixing them thoroughly and evenly, transferring them into a ceramic crucible, placing them in a muffle furnace for heating under air atmosphere, then cooling them naturally to room temperature, and grinding them into powder, namely P-melem;

[0015] S3, weigh B-melem and P-melem respectively, grind and mix them with potassium chloride and lithium chloride, put them into a Ganyu boat, place them in a muffle furnace and heat them under a nitrogen atmosphere, then wait for the temperature to naturally cool to room temperature, add deionized water to the calcined product, and filter and remove most of the potassium chloride and lithium chloride in the product after ultrasonic dispersion;

[0016] S4. The product is dissolved in deionized water and ultrasonically dispersed again. The water is heated to boiling under stirring and then filtered again to further remove potassium chloride and lithium chloride in the product. After vacuum drying, a B-CN / P-CN homogeneous heterojunction is constructed.

[0017] Furthermore, the mass ratio of melamine to sodium tetraphenylborate in S1 is 8:0.05, and the muffle furnace is heated at 12°C·min -1 The temperature was raised to 450°C and kept constant for 4 h.

[0018] Furthermore, the mass ratio of melamine to sodium dihydrogen phosphate in S2 is 8:0.2, and the muffle furnace is heated at 12°C·min -1 The temperature was raised to 450°C and kept constant for 4 h.

[0019] Furthermore, the mass ratio of B-melem to P-melem in S3 is 1:1.

[0020] Furthermore, the mass ratio of potassium chloride to lithium chloride in S3 is 11:9.

[0021] Furthermore, the nitrogen atmosphere flow rate in S3 is 200 mL min -1 , muffle furnace at 12℃·min -1 The temperature was raised to 550°C and kept constant for 4 h.

[0022] Furthermore, the vacuum drying temperature in S4 is 55-65°C.

[0023] The second object of the present invention is to provide a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion.

[0024] The third object of the present invention is to provide a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion for use in photocatalytic degradation of rhodamine B RhB.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention discloses for the first time a method for constructing a homogeneous B-CN / P-CN heterojunction with localized electronic differences and uniform dispersion by a simple pre-doping and molten salt-assisted two-step calcination method, which generates additional acceptor impurities and donor impurities in heptazine, thereby changing the electronic structure of carbon nitride, and the band bending at the interface of B-CN and P-CN forms an internal electric field, thereby promoting the directional migration of photogenerated carriers and the separation efficiency of photogenerated carriers, greatly improving its photocatalytic performance. Under visible light irradiation, the B-CN / P-CN material constructed by the present invention exhibits excellent photocatalytic degradation of RhB. After 60 minutes of illumination, the degradation rate of RhB is as high as 97.5%, and the degradation rate constant is 1.5 times that of pure phase CN, and it can still maintain good stability after multiple cycles.

[0027] 2. The B-CN / P-CN homogeneous heterojunction synthesized by the present invention has a tight interface effect, which provides a guarantee for the effective transmission of photogenerated charges. In the performance test, XRD, FTIR, XPS, DRS, electrochemistry, etc. were used to characterize the B-CN / P-CN homogeneous heterojunction constructed by the present invention to explore the migration path of photogenerated carriers. The results show that the doping of B and P did not change the main structure of the heptazine of carbon nitride, but changed the electronic structure of carbon nitride and improved the light absorption performance of bulk carbon nitride. The constructed B-CN / P-CN homogeneous heterojunction has low resistance to charge migration, has better electronic conduction performance and carrier transmission efficiency, promotes the separation efficiency of photogenerated carriers and the utilization rate of CN photogenerated carriers, and the photocatalytic performance is greatly improved.

[0028] 3. The present invention innovates the B-CN / P-CN homogeneous heterojunction that can be used for photocatalytic degradation of rhodamine B RhB. Under visible light irradiation, due to the potential difference, electrons are spontaneously transferred from the conduction band of P-CN to the conduction band of B-CN until the interface Fermi level is flat, thereby forming an electron depletion layer (+) and an electron accumulation layer (-) near the interface of P-CN and B-CN, and an internal electric field from P-CN to B-CN, which promotes the separation of CN photogenerated electrons and hole pairs, so that the electrons in the conduction band react with the dissolved oxygen in the RhB solution to generate O2 - , and holes can convert OH in the solution - Oxidized to ·OH, the final reaction system contains ·O2 - , OH and h + The active species degrade RhB into CO2 and H2O, achieving harmless degradation of the organic pollutant RhB. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 (a) XRD spectra and (b) FTIR spectra of CN, B-CN, P-CN and B-CN / P-CN samples in the performance test of the present invention;

[0030] Figure 2 The XPS spectra of the CN, B-CN, P-CN and B-CN / P-CN samples in the performance test of the present invention, wherein (a) is the high-resolution spectrum of C1s, (b) is the high-resolution spectrum of N1s; (c) is the high-resolution spectrum of B1s, and (d) is the high-resolution spectrum of P1s;

[0031] Figure 3 SEM images of CN (a), B-CN (b), P-CN (c) and B-CN / P-CN (d) samples in the performance test of the present invention;

[0032] Figure 4 (a) adsorption-desorption isotherms of CN and B-CN / P-CN samples in the performance test of the present invention; (b) pore size distribution diagram of CN and B-CN / P-CN samples;

[0033] Figure 5 (a) UV-visible diffuse reflectance spectra and (b) energy band spectra of CN, B-CN and P-CN samples in the performance test of the present invention;

[0034] Figure 6 (a) fluorescence spectra and (b) impedance spectra of different photocatalyst samples of CN, B-CN, P-CN and B-CN / P-CN in the performance test of the present invention;

[0035] Figure 7 (a) Degradation curves of different catalysts under visible light, (b) pseudo-first-order kinetic curves of CN, B-CN, P-CN and B-CN / P-CN samples in the performance test of the present invention, and (c) multiple test cycle diagrams and (d) free radical capture experiment diagrams of B-CN / P-CN samples;

[0036] Figure 8 Mott-Schottky curves of (a) CN, (b) B-CN and (c) P-CN samples in 0.2M Na2SO4 electrolyte at different frequencies in the performance test of the present invention, and schematic diagrams of the energy bands of the B-CN / P-CN sample (d) before and (e) after illumination. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with preferred embodiments. The endpoints of the ranges disclosed in the present invention and any values ​​are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be deemed to be specifically disclosed herein.

[0038] The experimental methods in the following examples, unless otherwise specified, are conventional methods and are performed according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0039] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0040] In the following performance tests, a D8 Advance X-ray powder diffractometer (XRD) (Cu Ka target) was used to determine the crystal structure of the catalyst, with an operating voltage of 40 kV and a current of 40 mA;

[0041] The following performance tests used a 50W 420nm LED lamp from Shenzhen Kiwi Optoelectronics Co., Ltd.;

[0042] In the following performance tests, the infrared spectra of the samples were measured using a Nicolet NEXUS 670 fast Fourier transform infrared spectrometer (FTIR), with 32 scans and a scanning band of 4000-400 cm -1 , resolution 4cm -1 ;

[0043] The constituent elements and valence states of the catalysts in the following performance tests were further collected and analyzed by the American Themo ScitntificK-Alpha X-ray photoelectron spectrometer (XPS); the morphology and structure of the catalysts were studied by the SU8010 scanning electron microscope (SEM); and the specific surface area and pore size distribution (BET) of the catalysts were analyzed by the American Micromeritics ASAP 2460 automatic physical and chemical adsorption instrument;

[0044] In the following performance tests, a Varian Cary 5000 UV-Vis-NIR spectrometer was used to test the ultraviolet visible diffuse reflectance spectrum (UV-Vis DRS) of the samples;

[0045] In the following performance tests, the FL / FS920 fluorescence spectrometer was used to test the steady-state fluorescence spectrum (PL) of the samples;

[0046] The following performance test used a standard three-electrode system to test the photoelectrochemical properties of the catalyst, with Ag / AgCl as the reference electrode and a Pt sheet electrode as the counter electrode. The sample was smeared on FTO (area: 0.283 cm 2 ) was used as the working electrode, the electrolyte was a 0.2 M Na2SO4 solution with a pH of 6.8, and the electrochemical impedance spectroscopy (EIS) and Mott-Schottky curves were performed on a Shanghai Chenhua CHI760E electrochemical workstation.

[0047] Example 1

[0048] This embodiment provides a method for constructing a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion, which specifically includes the following steps:

[0049] S1. Weigh 8 g of melamine and 0.05 g of sodium tetraphenylborate in a mortar, grind them, mix them thoroughly and transfer them into a 100 mL ceramic crucible. Place them in a muffle furnace in an air atmosphere at 12 °C min -1 The product was heated to 450°C at a heating rate of 10000 ℃ and kept at this temperature for 4 hours, then cooled naturally to room temperature, and the block product was ground into powder, namely B-melem;

[0050] S2, weigh 8g of melamine and 0.2g of sodium dihydrogen phosphate in a mortar, grind them, mix them thoroughly and evenly, transfer them into a ceramic crucible, place them in a muffle furnace and heat them under air atmosphere, then cool them naturally to room temperature and grind them into powder, namely P-melem;

[0051] S3. Weigh 0.3 g B-melem and 0.3 g P-melem respectively, grind and mix them with 3.3 g potassium chloride and 2.7 g lithium chloride, put them into a Ganyu boat and place them in a muffle furnace at a flow rate of 200 mL min -1 In nitrogen atmosphere at 12℃·min -1 The product was heated to 550°C at a heating rate of 1000 °C and kept at this temperature for 4 hours. The product was then cooled to room temperature naturally. Deionized water was added to the calcined product. The product was ultrasonically dispersed and filtered to remove most of the potassium chloride and lithium chloride in the product.

[0052] S4. The product was dissolved in deionized water and ultrasonically dispersed again. The water was heated to boiling under stirring and then filtered again to further remove potassium chloride and lithium chloride in the product. After vacuum drying at 60°C, a B-CN / P-CN homogeneous heterojunction was constructed.

[0053] The vacuum drying temperature can also be adjusted to 65° C. or 55° C. according to actual operating conditions.

[0054] Performance Testing

[0055] Preparation of CN, B-CN and P-CN samples:

[0056] First, weigh melamine and grind it in a mortar. After mixing thoroughly, transfer it into a 100 mL ceramic crucible and cover it with a lid. Place the crucible in a muffle furnace and heat it at 12 °C min-1 in an air atmosphere. -1 The sample was heated to 450°C at a rate of 100 °C and kept at this temperature for 4 h, then cooled naturally to room temperature. The block sample was ground into powder using an agate mortar and pestle for later use and named melem.

[0057] Then, 0.6 g of melem, B-melem, and P-melem were weighed, 3.3 g of potassium chloride, and 2.7 g of lithium chloride (mass ratio: 55%:45%) were placed in different mortars, and after being fully ground, they were transferred to different Ganyu boats. The Ganyu boats were placed in a muffle furnace and heated under a nitrogen atmosphere (flow rate: 200 mL min -1 ) at 12℃·min -1 The temperature was heated to 550°C at a rate of 100 °C and kept constant for 4 hours, then naturally cooled to room temperature;

[0058] Finally, the calcined samples were added to deionized water for ultrasonic dispersion and filtered several times to remove most of the potassium chloride and lithium chloride in the samples; the samples were ultrasonically dispersed in deionized water again, and the water was heated to boiling under stirring conditions using a heating stirrer. The boiling aqueous solution containing the samples was poured into a filtration device and filtered again to further remove the residual salt in the samples; all samples were dried in a vacuum oven at 60°C and named CN, B-CN and P-CN, respectively.

[0059] The B-CN / P-CN homogeneous heterojunction prepared in Example 1 was used as a B-CN / P-CN sample.

[0060] 1. Crystal structure characterization

[0061] The crystal structures of the prepared CN, B-CN, P-CN and B-CN / P-CN samples were characterized by XRD. Figure 1 As shown in (a), CN, B-CN, P-CN and B-CN / P-CN samples all have an obvious diffraction peak at 8° 2θ, and the corresponding spacing of the periodic repeating units in the plane is 1.099nm, which is shifted to a lower angle compared to the diffraction peak of bulk carbon nitride at 13° reported in the original literature, indicating that the polymerization degree of the conjugated structure of the two-dimensional plane of the carbon nitride polymer synthesized by this molten salt method is high and the in-plane flatness is good. In addition, the strong diffraction peak at 27.3° 2θ belongs to the (100) crystal plane of carbon nitride, which is considered to be a stacking of a layered conjugated system similar to graphite. At the same time, it was found that compared with CN, the diffraction peaks of B-CN, P-CN and B-CN / P-CN here showed signs of shifting to a lower angle, which was mainly due to the steric hindrance of the doped heptazine structure. It is worth noting that B-CN and B-CN / P-CN also have an obvious splitting peak at 2θ of 28°, which may be because the doping of B element leads to a decrease in the interlayer spacing and a strengthening of the interaction between layers.

[0062] Figure 1 (b) is the infrared spectrum (FTIR) of the sample, between 3500 and 3000 cm -1There is a broad absorption peak between 2167cm and 2167cm, which is mainly from the vibration of surface amino groups and adsorbed hydroxyl groups. -1 The absorption peak is attributed to the vibration of the cyano group, which is mainly caused by the loss of amino groups on the sample surface and the decomposition of some heptazine rings. -1 The absorption peak between 810cm and 810cm is mainly due to the vibration of the heptazine ring. -1 The vibration peak at is attributed to the fingerprint vibration of the azine ring. XRD and FTIR show that the doping of B and P does not change the main structure of the heptazine of carbon nitride.

[0063] 2. Characterization of element composition and chemical valence

[0064] XPS was used to characterize the elemental composition and chemical valence state of the prepared CN, B-CN, P-CN and B-CN / P-CN samples. Figure 2 (a) As shown in the high-resolution spectrum of C 1s, the peaks of all samples can be decomposed into three, located at 284.6, 286.4 and 288.1 eV, among which the peak at 288.1 eV is the strongest. The peaks at 286.4 and 288.3 eV are mainly from the sp 2 Hybridization, which is the main structure of polymer carbon nitride. The peak at 284.6eV is generally attributed to impurity carbon, such as grease. It is worth noting that, compared with CN, the binding energy of the peak attributable to the (NC=N) form in the B-CN sample is slightly reduced, while that of the P-CN is increased. The main reason for the change in binding energy is that the doping of B and P affects the local electron density. For N atoms, B atoms are electron-deficient, while P atoms are electron-rich.

[0065] Figure 2 In the high-resolution spectrum of N1s in (b), the peak at 398.8 eV is attributed to the sp 2 Hybridization (CN=C), the peak at 401.1eV is attributed to the ternary nitrogen N-(C)3 in the heptazine ring. These two structures of carbon atoms and nitrogen atoms are the main structures of the carbon nitride framework. The peak at 404.0eV indicates that the structure contains amino groups (CNH), which mainly exist on the surface of the sample.

[0066] Figure 2 In the high-resolution spectra of B1s and P1s in (c) and (d), the single peaks indicate that B and P in the B-CN, P-CN and B-CN / P-CN samples exist in the same form, namely BC and PC, respectively. It can be inferred that the doping atoms mainly replace the sp 2 In addition, the signal peaks of B and P in the sample also prove that B and P doped carbon nitride materials have been successfully synthesized.

[0067] 3. Characterization of morphology and specific surface area

[0068] Figure 3 The scanning electron microscope images of the prepared CN, B-CN, P-CN and B-CN / P-CN samples are shown in Figure 1. It can be seen from the figure that CN is a solid nanorod morphology with a length between 100-400nm and a diameter of about 40nm, which is roughly the same as previously reported in the literature. The morphology of B-CN, P-CN and B-CN / P-CN samples is roughly the same as that of CN, except that the length of the nanorods in the B-CN sample is slightly longer than that of CN. This shows that the doping of B and P has basically no effect on its morphology.

[0069] The effect of the construction of B-CN / P-CN homogeneous heterojunction on the specific surface area and pore size distribution of CN was analyzed by physical adsorption and desorption of N2. Figure 4 (a) The adsorption-desorption isotherms of the samples show that there is a hysteresis loop in the adsorption-desorption curves of CN and B-CN / P-CN, which are typical type IV adsorption curves, indicating that both are mesoporous materials. The specific surface area of ​​CN is about 63.1 m 2 g -1 , while the construction of B-CN / P-CN homogeneous heterojunction makes the specific surface area slightly reduced. Figure 4 (b) It can also be seen from the pore size distribution diagram of the samples that the pore size distributions of CN and B-CN / P-CN are mainly concentrated around 3.9nm and 15nm, but the pore size of B-CN / P-CN is smaller than that of CN. The reduction in pore size may be the main factor leading to the reduction in its specific surface area.

[0070] 4. Test of optical properties and separation performance of photogenerated electrons

[0071] The optical properties of the prepared CN, B-CN, P-CN and B-CN / P-CN samples were analyzed by UV-visible diffuse reflectance technique. Figure 5 In (a), it can be observed that the absorption band edges of B- and P-doped carbon nitride are shifted to longer wavelengths, indicating that the doping of B and P has successfully improved the light absorption performance of CN in the visible region. In addition, the band gap widths of CN, B-CN, and P-CN are estimated according to the Kubelka-Munk formula:

[0072] (αhν) 1 / n =A(hν-E g )

[0073] Where α represents the absorbance, h represents the Planck constant, ν is the photon frequency, and E g It is the photon energy band gap. The n value is related to the transition type of the catalyst electrons. CN belongs to an indirect band gap and its n value is 2.

[0074] According to the formula, with the Eg value as the x-axis and (αhν) 1 / n value as the y-axis, plot as shown in Figure 5 (b). When y = 0, extend the tangent line of the curve in the reverse direction to intersect with the x-axis, and the optical band gap value E g of the photocatalyst can be obtained. Thus, the band gaps of CN, B-CN, and P-CN are approximately 2.56 eV, 2.48 eV, and 2.52 eV, respectively.

[0075] 5. Fluorescence test and electrochemical test

[0076] Perform fluorescence tests and electrochemical tests on the prepared CN, B-CN, P-CN, and B-CN / P-CN samples. Figure 6 (a) is the fluorescence spectrum under the excitation of 360 nm excitation light. It can be seen from the figure that when B and P are doped into CN, the strong fluorescence peak at 460 nm attributed to the recombination of photo-generated electron-hole pairs is significantly weakened, and the fluorescence intensity of the B-CN / P-CN sample is further reduced. The experimental results show that the construction of the B-CN / P-CN homogeneous heterojunction promotes the separation of photo-generated electrons and holes in CN, thereby improving the utilization rate of photo-generated carriers in CN. Figure 6 (b) is the impedance spectrogram of different sample catalysts of CN, B-CN, P-CN, and B-CN / P-CN. The figure shows that the arc radius B-CN / P-C < P-CN < B-CN < CN, indicating that the resistance of charge migration of B-CN / P-CN is the lowest, with better electron conduction performance and carrier transport efficiency, which is consistent with the fluorescence characterization results.

[0077] 6. Photocatalytic performance analysis

[0078] First, add 0.05 g of the prepared CN, B-CN, P-CN, and B-CN / P-CN catalysts into the RhB solution (50 mL, 10 mg·L -1 -1) respectively. Place the reactor in a dark environment for 10 min to reach the adsorption-desorption equilibrium; then irradiate it with a 50 W λ = 420 nm LED lamp. Take 2 mL of the supernatant every 20 min, and after centrifugation, measure the absorbance at λ = 554 nm with a UV-visible spectrophotometer; finally, calculate the degradation rate within the corresponding time according to the absorbance value to investigate the photocatalytic degradation performance of different samples of CN, B-CN, P-CN, and B-CN / P-CN for RhB.

[0079] The photocatalytic degradation experiment of RhB follows the pseudo-first-order equation:

[0080] -ln(C / C0) = kt

[0081] Where: C is the solubility of the RhB solution at time t of the photoreaction; C0 is the concentration of the RhB solution at the beginning of the photoreaction; k is the pseudo-first-order apparent rate constant; t is the reaction time.

[0082] The degradation rate calculation formula is:

[0083] C=(1-C / C0)×100%

[0084] Where: C is the solubility of the RhB solution at time t of the photoreaction; C0 is the concentration of the RhB solution at the beginning of the photoreaction.

[0085] like Figure 7 As shown in (a), after 20 minutes of illumination, the degradation rate of CN on RhB is only 40%, and the degradation rate of carbon nitride is increased after B and P doping, while the degradation effect of B-CN / P-CN sample on RhB is significantly improved, with a degradation rate of 86%. After 60 minutes of illumination, the degradation rate of RhB is as high as 97.5%. Figure 7 (b) It can be seen that the apparent rate constants of RhB degradation by CN, B-CN, P-CN and B-CN / P-CN are 0.0375h -1 、0.0451h -1 , 0.0409h -1 , 0.0568h -1 , where the apparent rate constant of B-CN / P-CN is more than 1.5 times that of CN. The experimental results show that the construction of B-CN / P-CN homogeneous heterojunction is beneficial to improving the organic degradation performance of carbon nitride. From the previous characterization, it can be seen that the doping of B and P improves the light absorption performance of bulk carbon nitride. At the same time, the construction of homogeneous heterojunction further promotes the separation efficiency of photogenerated current, thereby greatly improving its photocatalytic performance.

[0086] To further explore the stability performance, a cycle experiment was conducted on the B-CN / P-CN sample. Figure 7 As shown in (c), after four cycles, the degradation activity of the B-CN / P-CN catalyst remained basically unchanged, and the degradation efficiency of RhB was still as high as 96.5%, indicating that B-CN / P-CN has high activity stability.

[0087] In addition, free radical capture experiments were carried out on B-CN / P-CN samples. 0.5 mL 0.5 mmol·L -1 Methanol (MeOH), isopropanol (IPA) and p-benzoquinone (p-BQ) were used as + , ·OH and ·O2 - The capture agent. Figure 7(d) It can be seen that after adding the capture agent, the degradation efficiency of B-CN / P-CN on RhB decreased from the original 97.5% to 78.4%, 60.3% and 50.1%, respectively, indicating that the O2 - and ·OH play a dominant role in the degradation of RhB, while h + Play a secondary role.

[0088] 8. Analysis of photocatalytic mechanism

[0089] The Mott-Schottky test was performed on the CN, B-CN and P-CN samples. Figure 8 As shown in (ac), the above three catalysts all show a curve with a positive slope, indicating that the photocatalyst is an n-type semiconductor material. It can be seen from the figure that the flat band potentials of CN, B-CN and P-CN relative to Ag / AgCl are -1.02V, -0.89V and -0.94V, respectively. According to the formula, the flat band potentials converted to the standard hydrogen electrode are -0.82V, -0.69V and -0.74V, respectively. According to previous literature reports, for n-type semiconductors, due to the relationship between the effective mass of electrons and the carrier concentration, the actual conduction band position is 0 to 0.1V higher than the flat band potential obtained by the test. In the present invention, according to experience, the difference between the actual conduction band value and the experimental value is set to 0.1V, so the final conduction band positions of CN, B-CN and P-CN are -0.92V, -0.79V and -0.84, respectively. Combined with the previous DRS test results, we can get the corresponding valence bands to be 1.64V, 1.69V and 1.68V, thus drawing the following Figure 8 (de) Schematic diagram of the energy bands of B-CN / P-CN before and after illumination.

[0090] From the previous characterization, it can be seen that the B-CN / P-CN photocatalyst synthesized by two-step thermal polymerization and molten salt-assisted synthesis is uniformly dispersed and has a tight interface effect, which provides a guarantee for the effective transmission of photogenerated charges. Under light, due to the potential difference, electrons spontaneously transfer from the conduction band of P-CN to the conduction band of B-CN until the interface Fermi level is flat, thereby forming an electron depletion layer (+) and an electron accumulation layer (-) near the interface of P-CN and B-CN, respectively. Therefore, an internal electric field is formed from P-CN to B-CN at the interface, which is conducive to the separation of photogenerated electrons and hole pairs. The electrons in the conduction band react with the dissolved oxygen in the RhB organic pollutant solution to generate ·O2 - , and holes can convert OH in the solution - Oxidized to ·OH, ·O2 in the reaction system - , OH and h + Active species ultimately degrade RhB organic pollutants into CO2 and H2O.

[0091] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. The terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprises a ..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.

[0092] The above are only preferred embodiments of the present application and do not constitute any form of limitation to the present application. Any technician familiar with the profession can make some changes or modify the technical contents disclosed above into equivalent embodiments with equivalent changes without departing from the scope of the technical solution of the present application. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application still fall within the scope of the technical solution of the present application.

Claims

1. A method for constructing a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion, characterized in that: A simple pre-doping and molten salt-assisted two-step calcination method was adopted. First, electron-deficient and electron-rich bodies were pre-doped in the precursor respectively to regulate the electronic structure of the carbon nitride intermediate. Then, a KCl / LiCl salt mixture was used as the liquid reaction medium to construct a B-CN / P-CN homogeneous heterojunction with localized electronic differences and uniform dispersion.

2. The method for constructing a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion according to claim 1, characterized in that: The specific steps include: S1. Weigh melamine and sodium tetraphenylborate, grind them in a mortar, mix them thoroughly and evenly, transfer them into a ceramic crucible, place them in a muffle furnace and heat them in an air atmosphere, then cool them naturally to room temperature, and grind them into powder, namely B-melem; S2, weighing melamine and sodium dihydrogen phosphate, grinding them in a mortar, mixing them thoroughly and evenly, transferring them into a ceramic crucible, placing them in a muffle furnace for heating under air atmosphere, then cooling them naturally to room temperature, and grinding them into powder, namely P-melem; S3, weigh B-melem and P-melem respectively, grind and mix them with potassium chloride and lithium chloride, put them into a Ganyu boat, place them in a muffle furnace and heat them under a nitrogen atmosphere, then add deionized water to the calcined product after it is naturally cooled to room temperature, and remove most of the potassium chloride and lithium chloride in the product by suction filtration after ultrasonic dispersion; S4. The product is dissolved in deionized water and ultrasonically dispersed again. The water is heated to boiling under stirring and then filtered again to further remove potassium chloride and lithium chloride in the product. After vacuum drying, a B-CN / P-CN homogeneous heterojunction is constructed.

3. The method for constructing a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion according to claim 2, characterized in that: The mass ratio of melamine to sodium tetraphenylborate in S1 is 8:0.05, and the muffle furnace is heated at 12°C·min -1 The temperature was raised to 450°C and kept constant for 4 h.

4. The method for constructing a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion according to claim 2, characterized in that: The mass ratio of melamine to sodium dihydrogen phosphate in S2 is 8:0.2, and the muffle furnace is heated at 12°C·min -1 The temperature was raised to 450°C and kept constant for 4 h.

5. The method for constructing a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion according to claim 2, characterized in that: The mass ratio of B-melem to P-melem in S3 is 1:

1.

6. The method for constructing a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion according to claim 2, characterized in that: The mass ratio of potassium chloride to lithium chloride in S3 is 11:

9.

7. The method for constructing a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion according to claim 2, characterized in that: The nitrogen atmosphere flow rate in S3 is 200 mL min -1 , muffle furnace at 12℃·min -1 The temperature was raised to 550°C and kept constant for 4 h.

8. The method for constructing a B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion according to claim 2, characterized in that: The vacuum drying temperature in S4 is 55-65°C.

9. A B-CN / P-CN homogeneous heterojunction with localized electron difference and uniform dispersion prepared according to any one of claims 1 to 8.

10. Use of a B-CN / P-CN homogeneous heterojunction having localized electron difference and uniform dispersion prepared by the method according to any one of claims 1 to 8 in photocatalytic degradation of rhodamine B RhB.